Non-Newtonian turbulent jets at low-Reynolds number - Soligo, Giovanni; Rosti, Marco Edoardo (International journal of multiphase flow, 2023)
We perform direct numerical simulations of planar jets of non-Newtonian fluids at low Reynolds number, in typical laminar conditions for a Newtonian fluid. We select three different non-Newtonian fluid models mainly characterized by shear-thinning (Carreau), viscoelasticity (Oldroyd-B) and shear-thinning and viscoelasticity together (Giesekus), and perform a thorough analysis of the resulting flow statistics. We characterize the fluids using the parameter γ, defined as the ratio of the relevant non-Newtonian time scale over a flow time scale. We observe that, as γ is increased, the jet transitions from a laminar flow at low γ, to a turbulent flow at high γ. We show that the different non-Newtonian features and their combination give rise to rather different flowing regimes, originating from the competition of viscous, elastic and inertial effects. We observe that both viscoelasticity and shear-thinning can develop the instability and the consequent transition to a turbulent flowing regime; however, the purely viscoelastic Oldroyd-B fluid exhibits the onset of disordered fluid motions at a lower value of γ than what observed for the purely shear-thinning Carreau fluid. When the two effects are both present, an intermediate condition is found, suggesting that, in this case, the shear-thinning feature is acting against the fluid elasticity. Despite the qualitative differences observed in the flowing regime, the bulk statistics, namely the centerline velocity and jet thickness, follow almost the same power-law scalings obtained for laminar and turbulent Newtonian planar jets. The simulations reported here are, to the best of our knowledge, the first direct numerical simulations showing the appearance of turbulence at low Reynolds number in jets, with the turbulent motions fully induced by the non-Newtonian properties of the fluid, since the Newtonian case at the same Reynolds number is characterized by steady, laminar flow. [Display omitted] •Non-Newtonian jets develop turbulence at low Reynolds.•Fluid elasticity and shear-thinning compete in the transition to turbulence.•Fluid elasticity promotes transition to turbulence at low Reynolds number.•Polymers show a different pathway for energy decay.